2020
DOI: 10.1101/2020.04.09.033522
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) envelope (E) protein harbors a conserved BH3-like sequence

Abstract: ANTI 6093263 STRUCT Q07817 Hs BCL2L1 109 EEYIKDCVFKDW-EELG--EEIRLKVFVLGGCR 138 PRO 16274670 STRUCT (pred) P88946 HHV8 VIRF1 163 RMLAALRRTRGL-QEIG--KGISQDGHHFLVFR 192 ANTI 22685405 STRUCT Q9DLD4 NDV F0 81 LDAYNRTLTTLL-TPLG--DSIRRIQESVTTSG 110 PRO 21810274 STRUCT Q9WBL3 NDV M 16 PSSSLLAFPIVL-QDTG--DGKKQITPQYRIQR 45 PRO 21810274 STRUCT Q6X1B6 NDV L 2111 EVTILGLRVKDL-NKVG--DVIGLVLRGMVSLE 2140 PRO 21810274 STRUCT (pred) Q00269 HCV CORE 108 GPTDPRRRSRNL-GKVI--DTLTCGFADLMGYI 137 PRO 19605477 MIX (pred) AAP73416 SARS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…Other tests revealed that Bcl-xL overexpression prevented the SARS-CoV E-induced death of Jurkat T cells (co-transfected with both SARS-CoV E and Bcl-xL cDNA). Further experiments showed that SARS-CoV E was able to interact with Bcl-xL through the BH3-like motif of SARS-CoV E and the BH3 domain of Bcl-xL [129] Recent bioinformatic analysis of Navratil et al [130] revealed structural homology between the C-terminal BH3-like motifs of SARS-CoV E and SARS-CoV-2 E. It suggested that SARS-CoV-2 E protein may also target Bcl-xL to affect the viability of infected cells [130].…”
Section: The Role Of Bcl-xl In Cov Infectionmentioning
confidence: 99%
“…Other tests revealed that Bcl-xL overexpression prevented the SARS-CoV E-induced death of Jurkat T cells (co-transfected with both SARS-CoV E and Bcl-xL cDNA). Further experiments showed that SARS-CoV E was able to interact with Bcl-xL through the BH3-like motif of SARS-CoV E and the BH3 domain of Bcl-xL [129] Recent bioinformatic analysis of Navratil et al [130] revealed structural homology between the C-terminal BH3-like motifs of SARS-CoV E and SARS-CoV-2 E. It suggested that SARS-CoV-2 E protein may also target Bcl-xL to affect the viability of infected cells [130].…”
Section: The Role Of Bcl-xl In Cov Infectionmentioning
confidence: 99%
“… 10 , 13 Subsequent entry of SARS-CoV-2 into a cell then triggers apoptosis via ectopic expression of the E protein and interaction between the C-terminal region of E protein and Bcl-xL, a member of the anti-apoptotic Bcl-2 family. 14 Ultimately, phagocytosis of the apoptotic cell by antigen presenting cells (APCs) occurs, specifically macrophages and dendritic cells. 9 Presentation by APCs leads to activation of the immune response and an increase in the release of inflammatory mediators, including IL-6, IL-10, G-CSF, and TNF-alpha.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis by SARS-COV-2: SARS-CoV-2 has four main structural proteins, Spike (S), Envelope (E), Nucleocapsid (N), and M membrane (M) 31 . SAR-COV-N protein cleavage is essential for viral replication, which depends on host cell caspase cleavage [32][33] .…”
Section: Structural Proteins Implicate Caspase Inducedmentioning
confidence: 99%
“…protein shares high sequence similarities to SARS-CoV-1 E protein, which is strongly conserved in Nterm regions and it is the smallest of all 8-12 kDa structural proteins [45][46] . SARS-CoV-2 E proteins share a conserved Bcl-2 Homology 3 (BH3)-like motif in their C-terminal region; a well-studied motif shown to be necessary for SARS-CoV E binding to Bcl-xL47; it has been found that apoptosis is promoted by Ectopic expression of SARS-CoV E 31 .…”
Section: Sars-cov-2 Envelope Protein: Sars-cov-2ementioning
confidence: 99%